(untitled) (Bulletin of the International Association for Paleodontology, 2025)
Until recently, there has been little prehistoric research to reveal the early arrival of modern humans on the north coast of Java, Indonesia. The focus of previous research has been more on the southern part of the island. Our research in the karst area of the Rembang Zone in the northern coast of Central Java has recovered human remains which offer potential new insights on the early occupation of Java Island by modern humans, especially during the Early-Mid Holocene. In this paper, we present the results of analyses of 29 dental specimens found in Gua Bedug, Rembang Residency. The analyses were conducted mainly to determine racial affinities based on dental metric and morphology. The results show that the human inhabitants of the Gua Bedug around 5.800 BP came from two population affinities, namely Australo-Melanesian and East Asian, highlighting the diversity of human inhabitants of the region during that period of time. The results also suggest that the occupation of the north coast of Java during the Plestocene-Holocene transition, around 12.000 BP, was more complex than previously thought.